1193. Comparison of the Clinical Outcomes of Patients With IMP-Type Carbapenemase-Producing Carbapenem-Resistant Enterobacteriaceae and Carbapenem-Sensitive Enterobacteriaceae in Japan. (26th November 2018) - Saito, Sho; Hayakawa, Kayoko; Ishikane, Masahiro; Tajima, Taichi; Matsunaga, Nobuaki; Ide, Satoshi; Kinoshita, Noriko; Kusama, Yoshiki; Fujitomo, Yumiko; Nakamoto, Takato; Toda, Yuta; Ohmagari, Norio
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) infections are spreading worldwide and have become a global menace. Different types of carbapenemases contribute to carbapenem resistance. The outcome of patients with IMP-type carbapenemase-producing CRE (IMP-CRE) is not well known. Methods: A matched case–control study from January 2012 to December 2016 was conducted at NCGM. All unique patients with IMP-CRE isolation were included and matched with carbapenem-sensitive Enterobacteriaceae (CSE) patients. Meropenem non-susceptible and/or ceftazidime-resistant Enterobacteriaceae, per CLSI criteria, were tested for metallo-β-lactamase production with further confirmation of bla IMP by PCR. Multivariate analyses were conducted for outcomes, adjusting for a propensity score predicting the likelihood of isolation of CRE vs. CSE. The balance of each group was determined by standardized biases <0.25 for variables on baseline characteristics. Results: In total, 192 patients (96 CRE, 96 CSE) were included (132 Enterobacter sp., 60 Klebsiella pneumoniae ). Isolations sites were sputum ( n = 76 [39.6%]), urine ( n = 62 [32.3%]), blood ( n = 22 [11.3%]), and wound ( n = 14 [7.2%]). The median age of the patients was 75 years [IQR: 66–84], and 109 (56.8%) were male. Thirty-one (32.3%) patients with CRE and 55 (57.3%) patients with CSE developed infections. The others were considered as colonization. qSOFA was positive (≥2) in seven patients with CRE infection and nine with CSE infection. In bivariate analysis, mortality and length of hospital stay (LOS) after CRE/CSE isolation were similar between the two groups, even after stratification by bacterial species and infection/colonization. After controlling for the propensity score (table), mortality and LOS remained similar between the two groups. Conclusion: IMP-CRE might not contribute to the worsened clinical outcomes when compared with CSE. Further evaluations are needed for additional outcome parameters. Disclosures: All authors: No reported disclosures.